Pengaruh Loss Ratio, Pertumbuhan Premi Neto, Tato Terhadap Risk Based Capital Perusahaan Asuransi Umum Konvensional - Sari, Juliani Lisma; Marlina, Ropi; Farhana, Shiva Evi (BanKu: Jurnal Perbankan dan Keuangan, 2025)
The purpose of this study is to determine the effect of Loss Ratio, Net Premium Growth, and Total Asset Turnover (TATO) on Risk-Based Capital (RBC). The population and sample in this study are the financial statements of Conventional General Insurance Companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023, so that as many as 60 companies' data were obtained, with the sampling technique used being saturated samples. The analysis method used was panel data regression analysis. Data processing in this study uses the Eviews 13 tool. The results of the study partially show that the Loss Ratio or Claim Expense Ratio, Net Premium Growth, and Total Asset Turnover (TATO) do not affect Risk-Based Capital (RBC). Simultaneously, Loss Ratio or Claim Expense Ratio, Net Premium Growth, and Total Asset Turnover (TATO) do not affect Risk-Based Capital (RBC).